Differentially Severe Cognitive Effects of Compromised Cerebral Blood Flow in Aged Mice: Association with Myelin Degradation and Microglia Activation - Wolf, Gilly; Lotan, Amit; Lifschytz, Tzuri; Ben-Ari, Hagar; Kreisel Merzel, Tirzah; Tatarskyy, Pavel; Valitzky, Michael; Mernick, Ben; Avidan, Elad; Koroukhov, Nickolay; Lerer, Bernard (Frontiers in Aging Neuroscience, 2017)
Bilateral common carotid artery stenosis (BCAS) models the effects of compromised cerebral blood flow on brain structure and function in mice. We compared the effects of BCAS in aged (21 month) and young adult (3 month) female mice, anticipating a differentially more severe effect in the older mice. Four weeks after surgery there was a significant age by time by treatment interaction on the radial-arm water maze (p=0.014): On the first day of the test latencies of old mice were longer compared to the latencies of young adult mice, independent of BCAS. However, on the second day of the test, latencies of old BCAS mice were significantly longer than old control mice (p=0.049), while latencies of old controls were similar to those of the young adult mice, indicating more severe impairment of hippocampal dependent learning and working memory by BCAS in the older mice. Fluorescence staining of myelin basic protein (MBP) showed that old age and BCAS both induced a significant decrease in fluorescence intensity. Evaluation of the number oligodendrocyte precursor cells demonstrated augmented myelin replacement in old BCAS mice (p<0.05) compared with young adult BCAS and old control mice. While microglia morphology was assessed as normal in young adult control and young adult BCAS mice, microglia of old BCAS mice exhibited striking activation in the area of degraded myelin compared to young adult BCAS (p<0.01) and old control mice (p<0.05). These findings show a differentially more severe effect of cerebral hypoperfusion on cognitive function, myelin integrity and inflammatory processes in aged mice. Hypoperfusion may exacerbate degradation initiated by aging, which may induce more severe neuronal and cognitive phenotypes.